DYNAMIC BEHAVIOR OF NON - RETURN VALVES OPERATING AT SMALL OPENING (Journal of Engineering, 2010)
In the present work a general dynamic behavior of non return valves subjected to jet flow is presented. The differential equations of valve motion and discharge were developed in a non-dimensional from, in terms of suitable dimensionless variables and parameters of the valve system.The derived equations are coupled nonlinear differential equations. Thus, a computer program was developed using a package called (MatLab) to solve these equations. The study shows that there are three types of the valve responses depending on the overall hydrostatic pressure difference and it is found that the valve vibrating at a constant limit cycle, which is leading to the failure of the system. It is also shown that the limit cycle frequency decreases with increasing the stiffness parameter and inertia factor. Finally the study shows that the losses factor has negligible effect on valve vibration and discharge.